2021
DOI: 10.1002/tre.791
|View full text |Cite
|
Sign up to set email alerts
|

Pornography and its impact on the sexual health of men

Abstract: Increased internet access has been accompanied by increased numbers of adolescent and adult men viewing online pornography, and there is growing concern about how this may affect their sexual development, sexual function, mental health and intimate relationships. This paper briefly reviews men's relationship with porn and the possible impact on sexual function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 25 publications
2
13
0
Order By: Relevance
“…This finding agrees with our observation that lockdowns are positively associated with increased pornography use. In different hypotheses, decreased sexual satisfaction owing to unrealistic expectations of sexual partners and performance may be caused by long-term pornography use [ 37 ]. It was suggested that this effect of pornography use is associated with a changed brain reward circuit in response to pornography, as the real-life situation may not be as ideal, novel and attractive as online pornography [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding agrees with our observation that lockdowns are positively associated with increased pornography use. In different hypotheses, decreased sexual satisfaction owing to unrealistic expectations of sexual partners and performance may be caused by long-term pornography use [ 37 ]. It was suggested that this effect of pornography use is associated with a changed brain reward circuit in response to pornography, as the real-life situation may not be as ideal, novel and attractive as online pornography [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Participants were guaranteed anonymity, and safeguards were implemented to prevent multiple submissions. Informed consent was obtained by participants' checking boxes attesting (1) to their current age being ≥18 years, and (2) to their informed consent before accessing the questionnaire. Respondents were notified that they could end participation at any time by closing the webpage.…”
Section: Methodsmentioning
confidence: 99%
“…With increasing access to the Internet, traditional barriers to sexually explicit materials such as public stigma and societal restriction have waned considerably over the past 20 years. Concomitantly, the number and variety of pornographic websites have greatly increased and, in some parts of the world, the viewing of pornography has become commonplace [1][2][3]. Even in geo-cultural regions having strong interdictions against pornography, access and use have increased steadily over the past 10 years among both men and women, and in particular among sexually diverse individuals [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are important points to consider, and erroneous information is readily available to our patients who need reassurance with facts. The source of information is important: the media and mediums such as pornography are commonly viewed and believed by many men (not just adolescents), and there is emerging evidence that watching pornography may have a detrimental effect on erectile function 20 …”
Section: Penile Anomaliesmentioning
confidence: 99%